Validation of the Supplemented Spetzler-Martin Grading System for Brain Arteriovenous Malformations in a Multicenter Cohort of 1009 Surgical Patients. Issue 1 (22nd September 2014) - Kim, Helen; Abla, Adib A.; Nelson, Jeffrey; McCulloch, Charles E.; Bervini, David; Morgan, Michael K.; Stapleton, Christopher; Walcott, Brian P.; Ogilvy, Christopher S.; Spetzler, Robert F.; Lawton, Michael T.
Abstract: BACKGROUND: The supplementary grading system for brain arteriovenous malformations (AVMs) was introduced in 2010 as a tool for improving preoperative risk prediction and selecting surgical patients. OBJECTIVE: To demonstrate in this multicenter validation study that supplemented Spetzler-Martin (SM-Supp) grades have greater predictive accuracy than Spetzler-Martin (SM) grades alone. METHODS: Data collected from 1009 AVM patients who underwent AVM resection were used to compare the predictive powers of SM and SM-Supp grades. Patients included the original 300 University of California, San Francisco patients plus those treated thereafter (n = 117) and an additional 592 patients from 3 other centers. RESULTS: In the combined cohort, the SM-Supp system performed better than SM system alone: area under the receiver-operating characteristics curve (AUROC) = 0.75 (95% confidence interval, 0.71–0.78) for SM-Supp and AUROC = 0.69 (95% confidence interval, 0.65-0.73) for SM ( P < .001). Stratified analysis fitting models within 3 different follow-up groupings (<6 months, 6 months-2 years, and >2 years) demonstrated that the SM-Supp system performed better than SM system for both medium (AUROC = 0.71 vs 0.62; P = .003) and long (AUROC = 0.69 vs 0.58; P = .001) follow-up. Patients with SM-Supp grades ⩽6 had acceptably low surgical risks (0%-24%), with a significant increase in risk for grades >6 (39%-63%). CONCLUSION: This study validates the predictive accuracy of the SM-Supp system in a multicenter cohort. An SM-Supp grade of 6 is a cutoff or boundary for AVM operability. Supplemented grading is currently the best method of estimating neurological outcomes after AVM surgery, and we recommend it as a starting point in the evaluation of AVM operability.